Comparative Effectiveness and Safety of High-Intensity Focused Ultrasound for Uterine Fibroids: A Systematic Review and Meta-Analysis - Wang, Yi; Geng, Jinsong; Bao, Haini; Dong, Jiancheng; Shi, Jianwei; Xi, Qinghua (Frontiers in Oncology, 2021)
Background Uterine fibroids are common benign tumors among premenopausal women. High intensity focused ultrasound (HIFU) is an emerging non-invasive intervention which uses the high intensity ultrasound waves from ultrasound probes to focus on the targeted fibroids. However, the efficacy of HIFU compared with other common treatment types in clinical procedure remains unclear. Objectives To investigate the comparative effectiveness and safety of HIFU with other techniques which have been widely used in clinical settings. Methods We searched Cochrane Central Register of Controlled Trials, PubMed, EMBASE, Cumulative Index to Nursing & Allied Health Literature, Web of Science, ProQuest Nursing & Allied Health Database, and three Chinese academic databases. Randomized controlled trials, non-randomized controlled trials and cohort studies were included. Primary outcome was rate of re-intervention and the GRADE approach was used to interpret the findings. Results 18 studies met the inclusion criteria. HIFU was associated with increased risk of re-intervention rate when compared with myomectomy (pooled OR 4.05, 95% CI 1.82 to 8.99). Results favored HIFU when compared with hysterectomy on change of follicle stimulating hormone (pooled MD-7.95, 95% CI -8.92 to 6.98), luteinizing hormone (MD -4.38, 95% CI-5.17 to -3.59) and estradiol (pooled MD 43.82, 95% CI 36.92 to 50.72). HIFU had a shorter duration of hospital stay compared with myomectomy (pooled MD -4.70, 95% CI -7.46 to -1.94, P<0.01). HIFU had lower incidence of fever (pooled OR 0.15, 95% CI 0.06 to 0.39, P<0.01) and less incidence of major adverse events (pooled OR 0.04, 95% CI 0.00 to 0.30, P<0.01) than hysterectomy. Conclusions HIFU helps to maintain femininity and shorten the length of hospital stay. High quality clinical studies with large sample size, long term follow-up and newest HIFU treatment protocol are suggested to be performed to evaluate the re-intervention rate. Clinical decision should be based on the specific situation of the patients and individual values.